PENDIDIKAN DENGAN KEBIJAKAN NASIONAL - Sukari; Ikke Fitriana Nugrahini; Salma Navi’ati Kholisa Dewi; Ahmad Suparno Basri (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
National Education Standards are minimum criteria regarding the education system in all jurisdictions of the Unitary State of the Republic of Indonesia. The policy on National Education Standards is contained in Government Regulation No. 19 of 2005. This regulation is an elaboration of Law Number 20 of 2003 concerning the National Education System. And along with the implementation of the 2013 curriculum, the policy changed to Government Regulation Number 32 of 2013 concerning Amendments to Government Regulation Number 19 of 2005 concerning National Education Standards. The National Education Standards contain 8 minimum criteria which include: graduate competency standards, content standards, process standards, teacher and education personnel standards, facilities and infrastructure standards, management standards, financing standards, education assessment standards.